Peran Digital Customer Experience dan Customer Engagement terhadap Brand Loyalty pada Generasi Z - Heru Yulianto (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study aims to analyze the influence of Digital Customer Experience (DCE) and Customer Engagement (CE) on Brand Loyalty (BL) among Generation Z, a digital-native cohort that plays a strategic role in shaping market dynamics in the digital era. Using a quantitative explanatory research design, data were collected through a structured questionnaire employing a 5-point Likert scale, distributed to 100 purposively selected respondents aged 18–27 who actively interact with brands through digital platforms. Multiple linear regression analysis was applied with SPSS software to test the hypotheses. The results reveal that Digital Customer Experience has a positive and significant impact on Brand Loyalty, indicating that seamless, personalized, and satisfying digital interactions enhance consumer loyalty. Similarly, Customer Engagement exerts a positive and significant influence on Brand Loyalty, emphasizing the role of active customer participation in strengthening emotional attachment and long-term commitment to brands. Jointly, both variables explain over 70% of the variation in Brand Loyalty, underscoring their synergistic effect in driving repurchase intention and advocacy behaviors among Generation Z. The findings provide both theoretical implications for enriching the customer experience–engagement–loyalty framework and practical guidance for marketers to optimize digital touchpoints, foster interactive engagement, and design loyalty-driven strategies tailored to Generation Z’s behavioral patterns in the digital marketplace.